Clinical application of medical exome sequencing for prenatal diagnosis of fetal structural anomalies. (August 2020) - Chen, Min; Chen, Jingsi; Wang, Chunli; Chen, Fei; Xie, Yinong; Li, Yufan; Li, Nan; Wang, Jing; Zhang, Victor Wei; Chen, Dunjin
Abstract: Objective: To evaluate the clinical application of medical exome sequencing (MES) for prenatal diagnosis of genetic diseases related to fetal structural anomalies detected by prenatal ultrasound examination. Study design: A total of 105 fetuses with structural anomalies were negative results in both Quantitative fluorescent polymerase chain reaction (QF-PCR) and chromosomal microarray analysis (CMA). Then trio-based MES was further used for identifying the potential monogenic diseases in these fetuses. Coding regions and known pathogenic non-coding regions of over 4000 disease-related genes were interrogated, and variants were classified following the guidelines of American College of Medical Genetics (ACMG). Results: The 105 fetuses with structural anomalies were categorized into 12 phenotypic groups. A definitive diagnosis was achieved in 19% (20/105) of the cases, with the identification of 21 pathogenic or likely pathogenic variants in 14 genes. The proportion of patients with diagnostic genetic variants varied between the phenotypic groups, with the highest diagnostic yield in the cardiovascular abnormalities (44%), followed by the skeletal and limb abnormalities (38%) and brain structural abnormalities (25%). In addition, 12 fetuses were detected variants of unknown significance (VOUS), while the relevance of phenotypes and variants would further evaluated. Conclusion: MES can identify the underlying genetic cause in fetal structural anomalies. It can further assist the management of pregnancy and genetic counseling. It was demonstrated the importance of translating prenatal MES into clinical practice.